Preparation, structural characterization, and performance evaluation of antler plate collagen peptide-calcium chelates - Baiqiang Wu; Jianing Sun; Yu Jiao; Mei Yang; Mengjie Dong; Wei Hu (Journal of Functional Foods, 2025)
This study investigated the preparation conditions, stability, calcium absorption characteristics, anti-osteoporotic activity, and chelation properties of antler plate collagen peptide‑calcium chelates (APCP-Ca). The high-affinity calcium chelate peptide monomer was isolated and purified from APCP-Ca, and its structure was characterized by molecular docking, molecular dynamics simulation, scanning electron microscopy, atomic force microscopy, X-ray spectroscopy and Fourier transform infrared spectroscopy. The results indicated that the optimal chelation conditions for APCP-Ca were as follows: peptide-to‑calcium ratio of 3:1, temperature of 50 °C, time of 50 min, and pH of 7.0. APCP-Ca exhibited thermal stability and pH stability, enhanced calcium transport in Caco-2 cells, and regulated key serum bone turnover markers, improving bone density in osteoporotic rats. A novel calcium-chelating peptide monomer GG10-Ca was obtained from APCP-Ca. The structural characterization results demonstrated that GG10-Ca was a novel and more densely packed crystal structure. APCP-Ca is a new type of calcium supplement with high bioavailability.